Baseline Cerebral Ischemic Core Quantified by Different Automatic Software and Its Predictive Value for Clinical Outcome - Shi, Zhang; Li, Jing; Zhao, Ming; Zhang, Minmin; Wang, Tiegong; Chen, Luguang; Liu, Qi; Wang, He; Lu, Jianping; Zhao, Xihai (Frontiers in Neuroscience, 2021)
Purpose: This study aimed to investigate the agreement of three software packages in measuring baseline ischemic core volume (ICV) and penumbra volume (PV) and determine their predictive values for unfavorable clinical outcome in patients with endovascular thrombectomy (EVT). Methods: Patients with acute ischemic stroke who underwent computed tomography perfusion (CTP) were recruited. Baseline CTP measurements including ICV and PV were calculated by three software packages of IntelliSpace Portal (ISP), Rapid processing of Perfusion and Diffusion (RAPID) and Fast-processing of ischemic stroke (F-STROKE). All patients received EVT and the modified Rankin scale (mRS) at 90 days after EVT was assessed to determine the clinical outcomes (favorable: mRS=0-2; unfavorable: mRS=3-6). The agreement of CTP measurements among three software packages was determined using intraclass correlation coefficient (ICC). The associations between CTP measurements and unfavorable clinical outcome were analysed using logistic regression. Receiver operating characteristic (ROC) curves were conducted to calculate the area under curve (AUC) of CTP measurements in predicting unfavorable clinical outcome. Results: Of 223 recruited patients (68.2±11.3 years old; 145 males), 17.0% had unfavorable clinical outcome after EVT. Excellent agreement between F-STROKE and RAPID was found in measuring ICV (ICC, 0.965; 95% CI, 0.956-0.973) and PV (ICC, 0.966; 95% CI, 0.956-0.973). ICVs measured by three software packages were significantly associated with unfavorable clinical outcome before (odds ratios: 1.012 to 1.018, all P<0.01) and after adjusted for confounding factors (odds ratios: 1.003 to 1.014, all P<0.05). In predicting unfavorable clinical outcome, ICV measured by F-STROKE showed similar performance to that measured by RAPID (AUC: 0.701 vs. 0.717) but higher performance than that measured by ISP (AUC: 0.629). Conclusions: The software of F-STROKE has excellent agreement with the widely used analysis tool of RAPID in measuring ICV and PV. The ischemic core volume measured by both F-STROKE and RAPID is a stronger predictor for unfavorable clinical outcome after EVT compared to ISP.